Exploring Sustainable Land Use in Monsoon Asia (Springer Geography,, 2018)
This book presents the outcome of the Towards Sustainable Land Use in Asia (SLUAS) project, which was the pilot undertaking for development in a series of projects on land use. Monsoon Asia, with its huge and still increasing population and rapid socioeconomic changes, is regarded as a major hot spot of global change in general and of land use change in particular. The major issues include urbanization, rural development, land-related problems such as food problems, and disasters in the context of global change and sustainability. Future Earth, the new international research framework established by International Council for Science (ICSU), the International Social Science Council (ISSC), and other international academic or funding organizations for a sustainable world, has chosen the Global Land Project (GLP) as one of the first such international projects it has endorsed that originated from International Geosphere/Biosphere Programme (IGBP) and/or International Human Dimensions Programme (IHDP). This endorsement is a clear indication of the importance of the issues related to land use and its changes. Land use change is an essential driving force of environmental change, a result of socioeconomic and environmental changes, and is a major environmental change itself. Because of this complex and multifaceted nature and the difficulties in obtaining relevant data with historical depth, this phenomenon has not been studied fully in the context of global change or sustainability. It is hoped that this book is of use to those who are concerned about the present and future land use in the world.